Preparation method of ceo2 modified ni fe2o4-based composite catalyst material for cracking co2
Patent Information
- Application Number
- CN202611214204.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-16
AI Technical Summary
表面烧结急剧降低了材料的比表面积和孔隙率,使得反应活性位点大量减少,氧化还原活性大幅衰减,最终导致催化剂的循环服役性能迅速恶化,无法满足工业化连续生产的需求
本发明通过将前驱体氧化镍、氧化铁和氧化铈共同进行湿磨处理,能够在室温条件下通过机械力化学作用使各组分前驱体在微观尺度上实现均匀混合和预活化,为后续高温固相反应中形成均一的CeO2改性的NiFe2O4基复合物奠定物相基础,同时CeO2组分的引入能够发挥物理阻隔和化学稳定作用,有效抑制NiFe2O4晶粒在高温下的生长和固相扩散,从而显著改善材料的抗烧结性能;通过将干燥、研磨、过筛后的均匀粉末混合物在氮气气氛下进行煅烧,惰性的氮气气氛能够防止前驱体在高温反应过程中被氧化性气氛干扰,确保铈元素以二氧化铈的第二相形式稳定存在于镍铁尖晶石主相晶界处,从而实现对主相结构的高效包覆和钉扎,最大化其抗烧结效果;通过将煅烧产物再次进行研磨和过筛,能够获得粒度均一、分散性良好的CeO2改性NiFe2O4基复合催化剂材料颗粒,增大了材料的反应接触面积,使其在两步法热化学循环裂解二氧化碳中能够充分接触反应气体,发挥出更高的氧交换效率和催化活性,从而大幅优化了催化剂的循环服役性能,并且整个制备流程简便、条件温和,便于实现规模化量产。
Smart Images

Figure CN122912864A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of inorganic composite oxide catalytic material preparation technology, and relates to a method for preparing CeO2-modified NiFe2O4-based composite catalyst material for CO2 cracking. Background Technology
[0002] With the acceleration of global industrialization, the massive consumption of fossil fuels has led to a continuous rise in the concentration of greenhouse gases, represented by carbon dioxide, in the atmosphere, triggering a severe climate change problem. The resource-based conversion of carbon dioxide, particularly its cracking into carbon monoxide with industrial value, is a crucial technological pathway to achieve carbon emission reduction and carbon recycling. Among numerous carbon dioxide conversion technologies, the two-step thermochemical cycle cracking technology has attracted significant attention due to its advantages, including direct utilization of clean heat sources such as solar energy, no need for precious metal catalysts, and easy separation of product gases. The core of this technology lies in the development of high-performance oxygen carriers or catalyst materials, whose redox activity directly determines the carbon dioxide cracking efficiency and cycle stability.
[0003] Among existing catalyst materials, nickel-iron spinel oxide (NiFe2O4) shows great potential in the two-step thermochemical cyclic cracking of carbon dioxide to produce carbon monoxide due to its high redox activity and oxygen-carrying capacity. The basic principle is that NiFe2O4 releases lattice oxygen to form a reduced state during the high-temperature reduction step, and then abstracts oxygen atoms from carbon dioxide in the lower-temperature oxidation step, causing it to crack into carbon monoxide, thus returning to its initial oxidation state and completing one cycle.
[0004] However, in practical applications, pure-phase NiFe2O4 materials face a fatal flaw. Under the high-temperature operating environment required for the two-step thermochemical cycle, the crystal structure of NiFe2O4 is prone to phase separation, decomposing into independent oxide phases such as nickel oxide and iron oxide. This irreversible phase separation disrupts the original spinel structure, leading to severe surface melting and aggregation of the material particles—a phenomenon known as sintering. Surface sintering drastically reduces the specific surface area and porosity of the material, resulting in a significant reduction in reactive sites and a substantial decrease in redox activity. Ultimately, this leads to a rapid deterioration in the catalyst's cyclic performance, making it unsuitable for continuous industrial production. Summary of the Invention
[0005] The purpose of this invention is to provide a method for preparing CeO2-modified NiFe2O4-based composite catalyst materials for CO2 cracking, so as to solve the above-mentioned problems.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing a CeO2-modified NiFe2O4-based composite catalyst material for CO2 cracking, characterized by comprising the following steps: After weighing the precursors NiO, Fe2O3 and CeO2, they were placed in a grinding jar, and agate balls and anhydrous ethanol were added. Wet grinding was then carried out to form a paste slurry. The resulting paste-like slurry was dried, ground, and sieved to obtain a powder mixture. The powder mixture was placed in a tube furnace and calcined under a nitrogen atmosphere; The calcined block sample was ground and sieved to obtain the CeO2-modified NiFe2O4-based composite catalyst material.
[0007] Furthermore, in terms of molar ratio, the ratio of NiFe2O4 to CeO2 in the precursor is 9:1 to 6:4.
[0008] Furthermore, the mass ratio of the agate ball to the total amount of the precursor is 1:1 to 3:1, and the mass ratio of the anhydrous ethanol to the total amount of the precursor is 1:1 to 3:1.
[0009] Furthermore, the wet milling is carried out in a high-speed planetary ball mill with a milling speed of 200~400 rpm and a milling time of 20~60 h.
[0010] Furthermore, the drying temperature is 90~150℃, and the drying time is 8~15h.
[0011] Furthermore, the calcination temperature is 1000~1600℃, the heating rate is 2~10℃ / min, and the holding time is 5~15h.
[0012] Furthermore, the grinding time is 10-30 minutes.
[0013] Secondly, the present invention provides a CeO2-modified NiFe2O4-based composite catalyst material for CO2 cracking, which is prepared by the aforementioned preparation method.
[0014] Furthermore, the molar ratio of NiFe2O4 to CeO2 in the composite catalyst material is 9:1 to 6:4.
[0015] Thirdly, the present invention provides a catalyst for two-step thermochemical cyclic cracking of CO2, comprising the CeO2-modified NiFe2O4-based composite catalyst material.
[0016] Compared with the prior art, the present invention has the following technical effects: This invention achieves uniform mixing and pre-activation of the precursors (nickel oxide, iron oxide, and cerium oxide) at the microscale through mechanochemical action at room temperature by wet milling. This lays the phase foundation for the formation of a uniform CeO2-modified NiFe2O4-based composite in the subsequent high-temperature solid-state reaction. Simultaneously, the introduction of CeO2 provides physical barrier and chemical stabilization, effectively inhibiting the growth and solid-state diffusion of NiFe2O4 grains at high temperatures, thus significantly improving the material's anti-sintering properties. Furthermore, the uniform powder mixture after drying, grinding, and sieving is calcined under a nitrogen atmosphere. The inert nitrogen atmosphere prevents the precursors from over-reacting at high temperatures. The process is interfered with by an oxidizing atmosphere, ensuring that cerium exists stably in the second phase form of cerium dioxide at the grain boundaries of the nickel-iron spinel main phase, thereby achieving efficient coating and pinning of the main phase structure and maximizing its anti-sintering effect. By grinding and sieving the calcined product again, CeO2-modified NiFe2O4-based composite catalyst particles with uniform particle size and good dispersibility can be obtained, increasing the reaction contact area of the material, enabling it to fully contact the reactant gas in the two-step thermochemical cyclic cracking of carbon dioxide, and exerting higher oxygen exchange efficiency and catalytic activity, thereby significantly optimizing the cyclic service performance of the catalyst. Moreover, the entire preparation process is simple and the conditions are mild, making it easy to achieve large-scale mass production. Attached Figure Description
[0017] Figure 1 This is a flowchart of the present invention. Detailed Implementation
[0018] The present invention will now be described in further detail with reference to the accompanying drawings: Example 1, see Figure 1 In one embodiment of the present invention, a method for preparing CeO2-modified NiFe2O4-based composite catalyst material for two-step thermochemical cyclic cracking of CO2 is provided. This method is used to prepare composite catalyst material with excellent anti-sintering performance and cycle stability, so as to solve the problem of deactivation of existing nickel ferrite materials due to surface sintering caused by phase separation during high-temperature cyclic cracking of carbon dioxide.
[0019] Specifically, the preparation method of the CeO2-modified NiFe2O4-based composite catalyst material for two-step thermochemical cyclic cracking of CO2 according to the present invention includes the following steps: S1: Weigh the precursors NiO, Fe2O3 and CeO2 and place them in a grinding jar. Add agate balls and anhydrous ethanol and perform wet grinding to form a paste slurry.
[0020] Nickel oxide and iron oxide are the starting materials for the nickel and iron sources required to form the target main phase nickel ferrite, while cerium oxide is the precursor of the modified component cerium dioxide. The three participate in the initial mixing, which, compared to synthesizing nickel ferrite first and then introducing cerium oxide, ensures that cerium is uniformly dispersed throughout the precursor system in the initial material construction stage. Agate balls are added as grinding media because agate has high hardness and good wear resistance, providing sufficient impact and shear forces during grinding, and is less likely to introduce metallic impurities into the material. The addition of anhydrous ethanol as a process control agent or dispersion medium enables the solid powder to form a uniform slurry system between the powder and the grinding balls. Its function is to reduce the surface tension of the powder during grinding, prevent cold welding and agglomeration of ultrafine powder, and transfer the mechanical energy of the grinding balls, resulting in a more uniform grinding effect. The wet milling process is the core operation. Utilizing the principles of mechanochemistry, it not only pulverizes large precursor particles into finer particles, but more importantly, through continuous collisions and friction, different types of oxide particles undergo repeated fracture and cold welding. This achieves premixing at the atomic or nanoscale and accumulates a large amount of lattice distortion and defects, reducing the activation energy of subsequent high-temperature solid-state reactions. The resulting paste-like slurry, formed after this step, is a state with suitable viscosity and flowability achieved by uniformly mixing solid powder and anhydrous ethanol, indicating that the wet milling process has reached an ideal degree of dispersion and mixing.
[0021] S2: Dry, grind, and sieve the obtained paste to obtain a powder mixture.
[0022] The purpose of the drying process is to heat the anhydrous ethanol in the paste-like slurry, causing it to absorb heat and evaporate completely. This allows the solid precursor to precipitate and deposit from the liquid suspension, transforming the flowing slurry into a dry, solid mass. During this drying process, the evaporation of anhydrous ethanol does not disrupt the homogeneous mixture of the components. The grinding process on the dried mass differs from the wet grinding in the previous step; this grinding is a dry pulverization, targeting the dried precursor agglomerates with a certain degree of binding force. The purpose of grinding is to break up these loose agglomerates or clumps, transforming them into a free-flowing powder and breaking down the physical bonds between larger particles that may have formed during the drying process. The sieving process involves screening the ground powder through a sieve with a specific mesh size. The aim is to establish a particle size threshold control, ensuring that only powder particles meeting the required size pass through, guaranteeing the high uniformity and dispersibility of the precursor powder entering the subsequent calcination process. Excessively large particles are trapped on the screen and removed, allowing subsequent high-temperature solid-phase reactions to take place in a uniform powder bed with consistent initial particle size, which is beneficial for controlling the phase composition and microstructure uniformity of the calcined product.
[0023] S3: Place the powder mixture in a tube furnace and calcine it under a nitrogen atmosphere.
[0024] The highly homogeneous powder mixture obtained in the previous step is transferred to a tube furnace. The tube furnace, as a heating device capable of providing a closed, controlled atmosphere and precise temperature program, is a suitable apparatus for this step. Choosing to perform calcination under a nitrogen atmosphere creates an inert gas protective environment, which plays a crucial role. The continuous flow of nitrogen effectively removes air, especially oxygen, from inside the furnace tube. At high temperatures, the presence of oxygen could lead to over-oxidation of partially reduced species or reaction with organic residues, causing uncertainties in the formed crystal structure. The chemical inertness of nitrogen ensures that the solid-phase reaction occurs only between the precursors themselves throughout the heating, holding, and cooling processes. Specifically, nickel oxide and iron oxide react to form the nickel-iron spinel phase, while cerium oxide does not participate in the main phase reaction. Instead, during spinel structure formation, it is distributed in situ as a second-phase inert component at the grain boundaries or grain surfaces of the main phase, thus achieving effective modification and physical isolation. Temperature and its variation during calcination are the fundamental energy sources driving atomic diffusion and phase formation. By controlling the temperature, atoms in the precursor powder gain sufficient energy for migration and rearrangement, thus transforming a simple oxide mixture into a composite oxide phase with a defined crystal structure. Finally, the powder mixture is sintered at high temperature into a hard, blocky sample, marking the near completion of the solid-state reaction of the target phase.
[0025] S4: Grind and sieve the block sample obtained by calcination to obtain the CeO2 modified NiFe2O4 based composite catalyst material.
[0026] The calcined block sample is a macroscopic body formed by the fusion and connection of countless tiny crystals at high temperatures. Although it already possesses the required CeO2-modified NiFe2O4-based composite phase structure, it must have the largest possible reactive specific surface area when used as a catalyst. The grinding operation is a physical crushing and deagglomeration process. By applying mechanical stress, the solid block sample is broken along weak areas such as grain boundaries, causing it to disintegrate into fine powder particles. This process directly determines the particle size and specific surface area of the final catalyst product. The sieving operation on the ground powder is another particle size classification and homogenization control through a sieve. It is similar in purpose to the sieving in step S2, but the object being processed is the finished catalyst powder. This operation ensures that the collected final product is CeO2-modified NiFe2O4-based composite catalyst material powder without large particles and with a uniform particle size distribution. After this step, the preparation process is completely closed-loop, and the product obtained is a catalyst material that can be directly used for two-step thermochemical cycle cracking of carbon dioxide.
[0027] This invention discloses a method for preparing CeO2-modified NiFe2O4-based composite catalyst materials for two-step thermochemical cyclic cracking of CO2. Through a de novo modification strategy, the cerium oxide precursor is blended and wet-milled with nickel oxide and iron oxide precursors constituting nickel ferrite at the source, ensuring that the components achieve uniform dispersion at the molecular level in the initial stage. This lays a solid foundation for the subsequent formation of a composite material with an ideal microstructure. High-temperature calcination under a nitrogen atmosphere promotes the smooth formation of the nickel-iron spinel phase under controlled conditions, while ensuring that cerium oxide is stably pinned at the grain boundaries as a second phase, synergistically constructing an internal framework with anti-sintering capabilities. Finally, by grinding and sieving the calcined product, a powdered catalyst product with controllable particle size and convenient for practical application is obtained. The entire preparation process is interconnected; the product state of each step directly forms the process basis for the next step. The process conditions of each core step synergistically achieve a significant improvement in the material's anti-sintering performance and simplification of the preparation process.
[0028] Example 2: A method for preparing a 9NiFe2O4-1CeO2 composite catalyst material for two-step thermochemical cyclic cracking of CO2, the specific steps of which are as follows: S1. Weigh the precursors NiO, Fe2O3 and CeO2 according to the ratio and place them in a grinding jar. Control the molar ratio of NiFe2O4:CeO2 to 9:1. Then add agate balls according to the mass ratio of agate balls to sample of 2:1. Finally, add anhydrous ethanol according to the mass ratio of anhydrous ethanol to sample of 1.5:1. S2. The sample was wet-milled in a high-speed planetary ball mill at 240 rpm with alternating forward and reverse rotation for 48 hours to form a uniform paste slurry. S3. Place the obtained paste sample in a drying oven and dry at 100°C for 10 hours. After fine grinding, filter using a 100-mesh filter to obtain the powder mixture required for the experiment; S4. Place the mixed powder material into a tube furnace and gradually heat it to 1400°C at a heating rate of 10°C / min under a nitrogen atmosphere, and continue calcining for 10 hours. S5. Grind the obtained block sample thoroughly for 20 minutes, then filter out large particles using a 100-mesh sieve to obtain the target product.
[0029] Example 3: A method for preparing an 8NiFe2O4-2CeO2 composite catalyst material for two-step thermochemical cyclic cracking of CO2, the specific steps of which are as follows: S1. Weigh the precursors NiO, Fe2O3 and CeO2 according to the ratio and place them in a grinding jar. Control the molar ratio of NiFe2O4:CeO2 to 8:2. Then add agate balls according to the mass ratio of agate balls to sample of 2:1. Finally, add anhydrous ethanol according to the mass ratio of anhydrous ethanol to sample of 1.5:1. S2. The sample was wet-milled in a high-speed planetary ball mill at 240 rpm with alternating forward and reverse rotation for 48 hours to form a uniform paste slurry. S3. Place the obtained paste sample in a drying oven and dry at 100°C for 10 hours. After fine grinding, filter using a 100-mesh filter to obtain the powder mixture required for the experiment; S4. Place the mixed powder material into a tube furnace and gradually heat it to 1400°C at a heating rate of 10°C / min under a nitrogen atmosphere, and continue calcining for 10 hours. S5. Grind the obtained block sample thoroughly for 20 minutes, then filter out large particles using a 100-mesh sieve to obtain the target product.
[0030] Example 4: A method for preparing a 7NiFe2O4-3CeO2 composite catalyst material for two-step thermochemical cyclic cracking of CO2, the specific steps of which are as follows: S1. Weigh the precursors NiO, Fe2O3 and CeO2 according to the ratio and place them in a grinding jar. Control the molar ratio of NiFe2O4:CeO2 to 7:3. Then add agate balls according to the mass ratio of agate balls to sample of 2:1. Finally, add anhydrous ethanol according to the mass ratio of anhydrous ethanol to sample of 1.5:1. S2. The sample was wet-milled in a high-speed planetary ball mill at 240 rpm with alternating forward and reverse rotation for 48 hours to form a uniform paste slurry. S3. Place the obtained paste sample in a drying oven and dry at 100°C for 10 hours. After fine grinding, filter using a 100-mesh filter to obtain the powder mixture required for the experiment; S4. Place the mixed powder material into a tube furnace and gradually heat it to 1400°C at a heating rate of 10°C / min under a nitrogen atmosphere, and continue calcining for 10 hours. S5. Grind the obtained block sample thoroughly for 20 minutes, then filter out large particles using a 100-mesh sieve to obtain the target product.
[0031] Example 5: A method for preparing a 6NiFe2O4-4CeO2 composite catalyst material for two-step thermochemical cyclic cracking of CO2, the specific steps of which are as follows: S1. Weigh the precursors NiO, Fe2O3 and CeO2 according to the ratio and place them in a grinding jar. Control the molar ratio of NiFe2O4:CeO2 to 6:4. Then add agate balls according to the mass ratio of agate balls to sample of 2:1. Finally, add anhydrous ethanol according to the mass ratio of anhydrous ethanol to sample of 1.5:1. S2. The sample was wet-milled in a high-speed planetary ball mill at 240 rpm with alternating forward and reverse rotation for 48 hours to form a uniform paste slurry. S3. Place the obtained paste sample in a drying oven and dry at 100°C for 10 hours. After fine grinding, filter using a 100-mesh filter to obtain the powder mixture required for the experiment; S4. Place the mixed powder material into a tube furnace and gradually heat it to 1400°C at a heating rate of 10°C / min under a nitrogen atmosphere, and continue calcining for 10 hours. S5. Grind the obtained block sample thoroughly for 20 minutes, then filter out large particles using a 100-mesh sieve to obtain the target product.
[0032] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing CeO2-modified NiFe2O4-based composite catalyst material for CO2 cracking, characterized in that, Includes the following steps: After weighing the precursors NiO, Fe2O3 and CeO2, they were placed in a grinding jar, and agate balls and anhydrous ethanol were added. Wet grinding was then carried out to form a paste slurry. The resulting paste-like slurry was dried, ground, and sieved to obtain a powder mixture. The powder mixture was placed in a tube furnace and calcined under a nitrogen atmosphere; The calcined block sample was ground and sieved to obtain the CeO2-modified NiFe2O4-based composite catalyst material.
2. The method for preparing the CeO2-modified NiFe2O4-based composite catalyst material for CO2 cracking according to claim 1, characterized in that, The molar ratio of NiFe2O4 to CeO2 in the precursor is 9:1 to 6:
4.
3. The method for preparing the CeO2-modified NiFe2O4-based composite catalyst material for CO2 cracking according to claim 1, characterized in that, The mass ratio of the agate ball to the total amount of the precursor is 1:1 to 3:1, and the mass ratio of the anhydrous ethanol to the total amount of the precursor is 1:1 to 3:
1.
4. The method for preparing the CeO2-modified NiFe2O4-based composite catalyst material for CO2 cracking according to claim 1, characterized in that, The wet milling is carried out in a high-speed planetary ball mill with a milling speed of 200~400 rpm and a milling time of 20~60 h.
5. The method for preparing the CeO2-modified NiFe2O4-based composite catalyst material for CO2 cracking according to claim 1, characterized in that, The drying temperature is 90~150℃, and the drying time is 8~15h.
6. The method for preparing the CeO2-modified NiFe2O4-based composite catalyst material for CO2 cracking according to claim 1, characterized in that, The calcination temperature is 1000~1600℃, the heating rate is 2~10℃ / min, and the holding time is 5~15h.
7. The method for preparing the CeO2-modified NiFe2O4-based composite catalyst material for CO2 cracking according to claim 1, characterized in that, The grinding time is 10-30 minutes.
8. A CeO2-modified NiFe2O4-based composite catalyst material for CO2 cracking, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 7.
9. The composite catalyst material according to claim 8, characterized in that, The molar ratio of NiFe2O4 to CeO2 in the composite catalyst material is 9:1 to 6:
4.
10. A catalyst for two-step thermochemical cyclic cracking of CO2, characterized in that, It includes the CeO2-modified NiFe2O4-based composite catalyst material as described in claim 8 or 9.